A Continuous Assay Set to Screen and Characterize Novel Protein N-Acetyltransferases Unveils Rice General Control Non-repressible 5-Related N-Acetyltransferase2 Activity - Asensio, Thomas; Dian, Cyril; Boyer, Jean-Baptiste; Rivière, Frédéric; Meinnel, Thierry; Giglione, Carmela (Frontiers in Plant Science, 2022)
Protein N-acetyltransferases (NATs) belong to the Gcn5-related N-acetyltransferases (GNATs) superfamily. GNATs catalyze the transfer of acetyl from acetyl-CoA to the reactive amine moiety of a wide range of acceptors. NAT sequences are difficult to distinguish from other members of the GNAT superfamily and there are many uncharacterized GNATs. To facilitate the discovery and characterization of new GNATs, we have developed a new continuous, non-radioactive assay. This assay is virtually independent of the substrate and can be used to get substrate specificity hints. We validated first the assay with the well-characterized Schizosaccharomyces pombe NatA (SpNatA). The SpNatA kinetic parameters were determined with various peptides confirming the robustness of the new assay. We reveal that the longer the peptide substrate the more efficient the enzyme. As a proof of concept of the relevance of the new assay, we characterized a NAA90 member from rice (Oryza sativa), OsGNAT2. We took advantage of an in vivo medium-scale characterization of OsGNAT2 specificity to identify and then validate in vitro several specific peptide substrates. With this assay, we reveal long-range synergic effects of basic residues on OsGNAT2 activity. Overall, this new, high-throughput assay allows better understanding of the substrate specificity and activity of any GNAT.